2018
DOI: 10.1002/mbo3.673
|View full text |Cite
|
Sign up to set email alerts
|

High‐production dairy cattle exhibit different rumen and fecal bacterial community and rumen metabolite profile than low‐production cattle

Abstract: Our aim was to simultaneously investigate the gut bacteria typical characteristic and conduct rumen metabolites profiling of high production dairy cows when compared to low‐production dairy cows. The bacterial differences in rumen fluid and feces were identified by 16S rDNA gene sequencing. The metabolite differences were identified by metabolomics profiling with liquid chromatography mass spectrometry ( LC ‐ MS ). The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
13
25
0
Order By: Relevance
“…These findings are in agreement with earlier study reporting reduction of dietary protein degradation under in vitro conditions when ryegrass grass was supplemented with rutin (68). In addition, studies have reported that lower Prevotella abundance has been observed in high producing cows as compared to low producing dairy cows (69). It is the most likely reason for higher milk yield and protein (%) observed in MLF45 as compared to other treatment groups.…”
Section: Milk Yield and Compositionsupporting
confidence: 92%
“…These findings are in agreement with earlier study reporting reduction of dietary protein degradation under in vitro conditions when ryegrass grass was supplemented with rutin (68). In addition, studies have reported that lower Prevotella abundance has been observed in high producing cows as compared to low producing dairy cows (69). It is the most likely reason for higher milk yield and protein (%) observed in MLF45 as compared to other treatment groups.…”
Section: Milk Yield and Compositionsupporting
confidence: 92%
“…The functional role of Quinella in the rumen fermentation of group Ctrl are yet to be explored. Compared with low-production dairy cows, the rumen fluid of high-production dairy cows was depleted of Anaeroplasma in Tenericutes [21]. As an opportunistic pathogen, the relative absence of Anaeroplasma in lambs fed forage rape might reduce the probability of inflammation in the rumen epithelium [22].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have looked at both rumen and fecal communities concurrently; however, one study, examining high- vs low-production dairy cattle, observed differences in the ruminal bacteria but not in the feces [41]. In another case, Dill-McFarland et al [42] found the effect of animal age strongly influenced both the rumen and fecal bacterial communities, but in adult cows only the rumen communities were affected by diet.…”
Section: Discussionmentioning
confidence: 99%